MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN PEMROSESAN HUJAN PADA ANAK TUNANETRA - FAJAR ROHMATILLAH, HUDAN; JOEDA ANDAJANI, SRI (Jurnal Pendidikan Khusus, 2019)
Abstract: Difficulties in understanding scientific concepts and processes result in the limited ability of blind children in the creation of concrete principles, totality, and independent activities in learning. The purpose of this study was to examine the effect of the problem based learning model on rain processing skills in blind children. The study design in this study used a pre-experimental study of one-group pretest-posttes because the study was conducted in one group without comparison. Based on the results of the pre-test it was found that the average scientific literacy ability of students was 40.27, then given treatment as many as 6 meetings, and in the post-test results obtained an average of 73.5 rain processing skills in blind children. It can be concluded that the use of problem based learning models in learning natural sciences has a positive influence on rain processing skills in blind children. Keywords: Problem Based Learning Model, Skills Rain Processing